2021
DOI: 10.3847/1538-4357/ac06a9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Water Snow Line in Magnetically Accreting Protoplanetary Disks

Abstract: The low water content of the terrestrial planets in the solar system suggests that the protoplanets formed within the water snow line. Accurate prediction of the snow line location moving with time provides a clue to constraining the formation process of the planets. In this paper, we investigate the migration of the snow line in protoplanetary disks whose accretion is controlled by laminar magnetic fields, which have been proposed by various nonideal magnetohydrodynamic (MHD) simulations. We propose an empiri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 103 publications
4
49
0
Order By: Relevance
“…However, recent studies of the magnetohydrodynamics of weakly ionized protoplanetary disks have shown that accretion heating favors the disk surface because the midplane region is too poorly ionized to sustain a large electric current (Hirose & Turner 2011;Mori et al 2019). These models predict that the magnetohydrodynamic accretion heating can raise the midplane temperature only when the disk opacity is high enough (Béthune & Latter 2020;Mori et al 2021). This suggests that stellar irradiation rather than internal heating may determine the location of the water snow line.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies of the magnetohydrodynamics of weakly ionized protoplanetary disks have shown that accretion heating favors the disk surface because the midplane region is too poorly ionized to sustain a large electric current (Hirose & Turner 2011;Mori et al 2019). These models predict that the magnetohydrodynamic accretion heating can raise the midplane temperature only when the disk opacity is high enough (Béthune & Latter 2020;Mori et al 2021). This suggests that stellar irradiation rather than internal heating may determine the location of the water snow line.…”
Section: Introductionmentioning
confidence: 99%
“…We take into account that a part of the mass accretion rate will not lead to heating, if the angular momentum is transported by large-scale disc winds (Mori et al 2021). Hence δ/α, with α representing the total angular transport and δ representing the local turbulence, gives the fraction of mass transported via turbulence and hence leading to heating.…”
Section: Protoplanetary Disc Modelmentioning
confidence: 99%
“…For disks around solar-type stars, they found that the snow line migrates inside 1 au within the first ∼ 10 5 yr after star formation. The classical viscous model also predicts inward migration of the snow line, but the snow line's arrival time at 1 au in the MHD disk model is an order of magnitude longer in the model assuming vertically uniform viscosity (see Figure 6 of Mori et al 2021). The MHD model suggests that planetary embryos at 1 au could have accreted a larger amount of water ice (see also Sato et al 2016), strongly constraining scenarios for the inner solar system formation.…”
Section: Introductionmentioning
confidence: 96%
“…Second, dust grains are the dominant source of disk opacity, and their size and spatial distribution control the disk's cooling rate (e.g., Oka et al 2011). Mori et al (2021) assumed that submicron-sized grains are abundant in the disks 1 ; however, it is more likely that most of the small grains in the inner few au region grow to larger solid particles or bodies in the first 1 Myr of disk evolution (e.g., Birnstiel et al 2010). As the abundance of small dust grains decreases, the ionization fraction increases, whereas the disk opacity decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation